2020
DOI: 10.1186/s12877-020-01870-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a patient-centred deprescribing procedure in older multimorbid patients in Swiss primary care - A cluster-randomised clinical trial

Abstract: Background Management of patients with polypharmacy is challenging, and evidence for beneficial effects of deprescribing interventions is mixed. This study aimed to investigate whether a patient-centred deprescribing intervention of PCPs results in a reduction of polypharmacy, without increasing the number of adverse disease events and reducing the quality of life, among their older multimorbid patients. Methods This is a cluster-randomised clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 65 publications
1
54
0
Order By: Relevance
“…It has undergone pilot testing in community pharmacies in Northern Ireland and England; whilst study procedures and intervention delivery were reported to be feasible, the authors plan to make modifications before progressing to a cluster RCT to explore intervention effectiveness [92]. Other approaches that have been utilised in interventions to support prescribing and medication use in older people include electronic clinical decision support systems [94,95] and deprescribing [96,97]. Whilst deprescribing interventions may reduce mortality and the use of potentially inappropriate medications, and improve medication adherence [96,98,99], the effect may not be sustained, and further research is needed to determine the optimal interval of repeated deprescribing interventions [97].…”
Section: Interventions To Support Medication Use In Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has undergone pilot testing in community pharmacies in Northern Ireland and England; whilst study procedures and intervention delivery were reported to be feasible, the authors plan to make modifications before progressing to a cluster RCT to explore intervention effectiveness [92]. Other approaches that have been utilised in interventions to support prescribing and medication use in older people include electronic clinical decision support systems [94,95] and deprescribing [96,97]. Whilst deprescribing interventions may reduce mortality and the use of potentially inappropriate medications, and improve medication adherence [96,98,99], the effect may not be sustained, and further research is needed to determine the optimal interval of repeated deprescribing interventions [97].…”
Section: Interventions To Support Medication Use In Older Adultsmentioning
confidence: 99%
“…Other approaches that have been utilised in interventions to support prescribing and medication use in older people include electronic clinical decision support systems [94,95] and deprescribing [96,97]. Whilst deprescribing interventions may reduce mortality and the use of potentially inappropriate medications, and improve medication adherence [96,98,99], the effect may not be sustained, and further research is needed to determine the optimal interval of repeated deprescribing interventions [97]. A multi-faceted intervention for primary care has been proposed that includes an adapted versio n of a deprescribing protocol which may reverse prescribing cascades [100].…”
Section: Interventions To Support Medication Use In Older Adultsmentioning
confidence: 99%
“…For instance, short‐term indirect effects include contamination bias associated with intervention implementation. In a cluster RCT in Switzerland 99 and a pre‐ and postintervention study in Japan, 100 deprescribing interventions were associated with a decrease in the number of medications used in the usual care group. It is possible that the implementation of polypharmacy interventions may have a desirable impact on culture and usual care at their institutions.…”
Section: Discussionmentioning
confidence: 99%
“…‐Patient‐centered deprescribing procedure is effective immediately after the intervention, but not after 6 and 12 months 99 …”
Section: Discussionmentioning
confidence: 99%
“…However, it may also be that physicians try not to prescribe complex treatments to physically and/or cognitively dependent older adults at their discharge, as they would probably struggle to manage them during this specific period. Therefore, our results may indicate growing concerns about prescriptive practices in Switzerland [ 54 ].…”
Section: Discussionmentioning
confidence: 99%